Использование международного опыта построения национального страхового законодательства с учетом вступления в ВТО (Путеводитель предпринимателя, 2020)
In work the basic arrangements on Russia’s accession to the World Trade Organization regarding insurance are stated, the basic restrictions which introduction is necessary for preservation of the national insurance market are considered, the international experience of providing of access of foreign insurers on the national insurance markets is considered.